TOPENG SUREALIS DALAM KARYA KERAMIK - M. Michael Duta; Suib Awrus (Serupa The Journal of Art Education, 2020)
The creation of an art starts with the existence of an idea and a thought that emerged from an artist. In this case, the author expand the idea in the form of ceramic works namely surreal masks. Furthermore, the creation of this art aims to visualize masks in ceramic work that use these methods: preparation, elaboration, synthesis, concept realization, and final finishing. The medium that was used in this work of art is clay. At the end of this work of art, there will be an exhibition for three days. The seven arts are titled with surreal masks; amongst them are two hyprocritical expressions, two pretentious expressions, and three existential expressions. The decision of the seven arts was adjusted with the theme Characteristic Attitude and Reflection of the Personality of Every Human Being. If we are comprehending and making lesson in every human personality, it would be found some identites in every behavior.Keywords: Surreal Masks, Ceramic Works, Pinching Technique